General Property Rights from Sharia Perspective: Strategy for the Implementation of Ummah's Economic Welfare and Justice - Nur Sillaturohmah Handayani; Sya'roni Sya'roni; Suhaimi Ab Rahman; Mr. Anat Maisu (Demak Universal Journal of Islam and Sharia, 2023)
This study aims to reveal the legal status of public property rights from the perspective of sharia and strategies for implementing economic welfare and justice for the ummah. The method used in this study is to use qualitative research with a library study. The results of the study show that in the Sharia perspective, there are three types of public property; mining goods (natural resources) which are unlimited in number, and public utilities, and assets which in their original state are forbidden to own personally. Public property status becomes weak when it is not returned to its original state from a Sharia perspective. Coupled with the support of the Law on Water Resources which has not given serious attention to the status of public property rights. The most influential aspect of opportunity in this matter is the potential of public property to create prosperity and economic justice in society. The effectiveness of implementing economic welfare and justice will be realized by restoring the status of public property according to its position in the perspective of Sharia and by applicable government regulations.